Agricultural commercialization, economic development, and nutrition - von Braun, Joachim; Kennedy, Eileen T. (International Food Policy Research Institute, 1994)
A large body of literature makes the argument that commercialization of agriculture has mainly negative effects on the employment, incomes, food production and consumption, health, and nutrition of the poor. In Commercialization of Agriculture, Economic Development, and Nutrition, Joachim von Braun and Eileen Kennedy find that the conclusion that commercialization of agriculture is generally bad for nutrition is flawed. This conclusion, emerging from a mix of historical, real, and ideological factors as well as methodologically faulty analysis, has continually been questioned by policymakers in developing countries as well as aid agencies and non-governmental organizations.